The role of quantum measurement in stochastic thermodynamics - Cyril Elouard (Nature Portfolio, 2017)
Rebuilding quantum thermodynamics on quantum measurement Measuring a quantum system is an ultimately random operation. It induces a genuinely quantum time arrow, increasing the system’s entropy. But because it perturbs its state, quantum measurement also provides energy to the quantum system. These energetic quantum fluctuations play the same role as thermal fluctuations in thermodynamics, while being of quantum nature. Building on such “Quantum Heat”, a group of scientists from france provided a thermodynamic analyzis of canonical experiments of quantum optics. They show that quantum heat is a major concept to evaluate the performances of a basic protocol to counteract the decoherence of a quantum bit. The findings pave the way towards a new generation of quantum engines, powered by quantum measurement. They bring new tools to investigate the energetic cost of quantum protocols performed at ultra-low temperature, in the presence of decoherence.